Coinherited Hemoglobin Lansing-Ramathibodi/Southeast Asian Deletional α0-thalassemia and Hemoglobin E Causing Falsely Low Oxygen Saturation on Pulse Oximetry - Chouymankong, Kornkamol; Arkarattanakul, Nattawan; Mankhemthong, Kanittha; Sirinam, Nisarat; Phusua, Arunee; Fanhchaksai, Kanda; Charoenkwan, Pimlak (Biomedical Sciences and Clinical Medicine, 2024)
Hemoglobin (Hb) variants resulting from mutations in globin genes and leading to qualitative abnormalities of globin proteins can result in a spectrum of clinical presentations. Herein we describe a case of a 10-year-old boy with an Hb variant, Hb Lansing-Ramathibodi (HBA1:c.264C>G, codon 87 His>Gln), who was incidentally found to have low pulse oximetry oxygen saturation readings (low SpO2). Laboratory investigations revealed mild microcytic anemia. Arterial blood gas showed normal partial pressure of oxygen (PaO2) and arterial oxygen saturation (SpO2) values, indicating an oxygen saturation gap. Subsequent Hb analysis identified an abnormal peak, prompting further molecular studies which confirmed the coinheritance of Hb Lansing-Ramathibodi, Southeast Asian deletional α0-thalassemia and the Hb E trait. The patient’s mother, carrying the Hb Lansing-Ramathibodi and Hb E traits without Southeast Asian deletional α0-thalassemia, was asymptomatic. This case underscores the importance of identifying and characterizing rare Hb variants presenting with an oxygen saturation gap for informed clinical management and genetic counseling.